Peroxisome proliferator–activated receptor delta and liver diseases - Tomoo Yamazaki; Edward E. Cable; Bernd Schnabl (Hepatology Communications)
Peroxisome proliferator-activated receptors (PPARs) are nuclear receptors involved in transcriptional regulation and play an important role in many physiological and metabolic processes. Unlike PPAR-alpha and PPAR-gamma, PPAR-delta is ubiquitously expressed, and its activity is key to maintaining proper metabolic homeostasis within the liver. PPAR-delta not only regulates physiologic processes of lipid, glucose, and bile acid metabolism but also attenuates pathologic responses to alcohol metabolism, inflammation, fibrosis, and carcinogenesis, and is considered an important therapeutic target in liver diseases. Promising results have been reported in clinical trials for PPAR-delta agonists in liver disease, and the selective agonist seladelpar was recently conditionally approved in the United States as a new treatment option for primary biliary cholangitis. This review provides an overview of PPAR-delta’s function and biology in the liver, examines its kinetics and therapeutic potential across different liver diseases, and discusses the current status of clinical trials involving its agonists.